Assessment of Mechanical Fetal PR Interval in Intrahepatic Cholestasis of Pregnancy and Its Relationship with the Severity of the Disease - Yakut, Kadriye; Öcal, Fatma Doğa; Öztürk, Merve; Öztürk, Filiz Halici; Oğuz, Yüksel; Çelen, Şevki (American Journal of Perinatology, 2019)
Objective This study aimed to investigate the fetal atrioventricular conduction system in intrahepatic cholestasis of pregnancy (ICP) by measuring the fetal mechanical PR interval and to explore the significance of predicting the severity of the disease.Study Design Forty pregnant women diagnosed with ICP, classified as severe and mild, and 40 healthy pregnant women participated in the study. Fetal mechanical PR interval was calculated, and fetal mechanical PR interval and neonatal outcome were compared between the groups. The relationship between the mechanical PR interval and the severity of ICP was analyzed.Results The fetal mechanical PR interval was significantly longer in the ICP group than in the control group (p < 0.005). Likewise, laboratory parameters such as transaminases (alanine aminotransferase [ALT], aspartate aminotransferase [AST]) and total bilirubin levels were significantly higher in the ICP group (p < 0.005).There were no statistically significant differences in the fetal complications. There was a positive correlation between the severity of disease and fetal PR interval.Conclusion A prolonged fetal mechanical PR interval in fetuses of mothers with ICP was demonstrated in this study. It was also shown that there was a positive correlation between fetal PR interval and severity of the disease. The study concluded that fetal mechanical PR interval measurement can be used to predict the severity of disease in ICP.
Keywords: fetal PR interval; intrahepatic cholestasis of pregnancy; cholestasis; transaminase; bile acid